The climate preferences of Irish tourists by purpose of travel - Seán Lyons; Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
We estimate a pooled travel model for the destination choice of tourists from the Republic of Ireland in 2006. We distinguish between holidaymakers (further split into travelling with children, elderly, and other), visitors to family, visitors to friends, business travellers and other travellers. We show that the different types of tourist have very different preferences. Elderly holidaymakers and family visitors stand out most from the 'average' tourist. Preferences for cultural heritage, population density, and temperature discriminate the most between tourist types. We find some evidence that destination preferences vary over the year, but limited data prevent a full investigation. All types of Irish tourists are indifferent to precipitation. Only holidaymakers respond to temperature differences. All holidaymakers dislike cold destinations, but only elderly holidaymakers dislike hot destinations as well.
Keywords: 330; Internationaler Tourismus; Klima; Urlaubsverhalten; Irland